Chaos and Bifurcation Control Using Nonlinear Recursive Controller - Harb, A. M.; Zohdy, M. A. (Nonlinear Analysis: Modelling and Control, 2002)
Chaos and bifurcation control is achieved by nonlinear controller that is able to mitigate the characteristics of a class of nonlinear systems that are experiencing such phenomenon. In this paper, a backstepping nonlinear recursive controller is presented. Comparison has been made between it and a Pole Placement controller. The study shows the effectiveness of the proposed control under various operating conditions.
Keywords: nonlinear theory; bifurcation; chaos; backstepping; pole placement; Lyapunov; control systems